2019
DOI: 10.1002/jper.18-0635
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative smoking exposure and cessation associated with the recurrence of periodontitis in periodontal maintenance therapy: A 6‐year follow‐up

Abstract: Background This study followed individuals in periodontal maintenance therapy (PMT) over 6 years and longitudinally evaluated the effects of cumulative smoking exposure and duration of smoking cessation on the recurrence of periodontitis. Methods From a 6‐year follow‐up cohort study with 212 individuals in PMT, 142 patients who attended at least one PMT visit within 12 months were determined to be elegible. According to smoking habits they were categorized into three groups: non‐smokers (NS; n = 95), former sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
(180 reference statements)
0
23
0
Order By: Relevance
“…ES: effect size The current systematic review did not evaluate treatment outcomes in former smokers. Studies have showed that smoking cessation can significantly improve clinical outcomes of both non-surgical and surgical periodontal treatments (Costa & Cota, 2019;Haber & Kent, 1992;Preshaw et al, 2005). Smoking intensity and duration can also affect clinical outcomes of periodontal therapies (Baljoon et al, 2005;Bergström et al, 2000;Kaldahl et al, 1996).…”
Section: F I G U R Ementioning
confidence: 99%
“…ES: effect size The current systematic review did not evaluate treatment outcomes in former smokers. Studies have showed that smoking cessation can significantly improve clinical outcomes of both non-surgical and surgical periodontal treatments (Costa & Cota, 2019;Haber & Kent, 1992;Preshaw et al, 2005). Smoking intensity and duration can also affect clinical outcomes of periodontal therapies (Baljoon et al, 2005;Bergström et al, 2000;Kaldahl et al, 1996).…”
Section: F I G U R Ementioning
confidence: 99%
“…When considering that high-risk patients are also those showing less adherence to the SPC program in the long term [25,[33][34][35], the adoption of a SPC program based on a more stringent (i.e., < 3-month) interval between sessions might represent a weak option to enhance SPC efficacy over time. Considering that patients with PerioRisk level 5 are significantly different in terms of smoking and disease-associated markers (Table 8), a more efficient treat-to-target approach based on smoking cessation program [36][37][38] as well as a more intense treatment of pockets and periodontal inflammation may be recommended prior to SPC enrollment in individuals at the highest risk level, particularly if not complying with the suggested SPC recall interval. This recommendation is also supported by previous data showing that high (≥ 30%) BoP score [8] and increasing proportions of bleeding pockets [4] at re-evaluation following active therapy were positively associated with greater tooth loss during SPC.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that smokers have a worse clinical response to non‐surgical periodontal treatment compared to non‐smokers (González et al., ; Heasman et al., ; Wan et al., ). A recent study investigating the effect of smoking during 6 years of periodontal maintenance showed that cumulative smoking exposure was significantly associated with the recurrence of periodontitis (Costa & Cota, ). This phenomenon appeared to be present also in the 2‐year SPT period, since the analysis showed that at sites PPD ≥ 4 mm and ≥5 mm at baseline, smokers were more likely to develop PPD increase and attachment loss overtime compared to non‐smokers in both groups.…”
Section: Discussionmentioning
confidence: 99%